Distributed sensor network system based on NFC technology - LIU YUAN; LI ZHENG; LI YAN; ZHANG NING (2015)
The invention discloses a distributed sensor network system based on the NFC technology. NFC devices, MCUs, SPI buses, I2C buses, local area network controllers, a main control computer, and an Internet device form an NFC distributed sensor network system. According to the system, each sensor unit formed by connecting one MCU and a plurality of NFC terminal devices in parallel through the SPI buses comprehensively senses attitude and position information of components. Multiple sensor units are connected in parallel to one I2C bus and controlled by one local area network controller, and form an NFC sensor local area network inside a warehouse. NFC sensor local area networks are interconnected by the Internet device to form the NFC distributed sensor network system which is controlled and managed by the main control computer in a unified manner. The system of the invention is advantageous in that close-range component location and detection is carried out by NFC, the anti-jamming capability is strong, and location is accurate; by adopting the SPI and I2C buses, control is convenient, and the communication rate is high; and a large-scale network can be built across regions by the Internet.